HETTANGIAN AMMONITES AND RADIOLARIANS IN THE MT. CAMICIA (GRAN SASSO, CENTRAL APENNINES) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Vallone di Vradda stratigraphic section is situated in the eastern part of the Gran Sasso range and shows the transition from Late Triassic euxinic facies to Early Liassic open pelagic facies. This paper describes Middle and Late Hettangian ammonite and radiolarian assemblages found in the upper part of the succession. The existence of an anoxic event below the Middle Hettangian beds is noted. Assemblages of small-sized Middle Hettangian ammonites suggest some taxonomic innovation within the early Lytoceratina: gen. n. (Pleuroacanthitidae) and Analytoceras n. sp. indet. Radiolarians found together with ammonites improve the knowledge of Hettangian radiolarian assemblages of the western Tethys.